Comparison of static, countermovement, and drop jumps of the upper and lower extremities in U.S. junior national team male gymnasts - Suchomel, T. J.; Sands, W. A.; McNeal, J. R. (Science of Gymnastics Journal, 2016)
Twenty-one gymnasts performed two repetitions each of upper (UE) and lower extremity (LE) static (SJ), countermovement (CMJ), and drop (DJ) jumps on a force platform. Average measures of maximum jump height (MXHT), peak force (PF), rate of force development (RFD), and peak power (PP) were calculated for analysis. In addition, sample-specific allometric scaling was used to scale PF and PP. Four 2x3 repeated measures ANOVAs were calculated for analyses. Statistically significant main effects were observed for UE vs LE for MXHT, PF, RFD, and PP (all p < 0.001). Statistically significant main effects for jump-type were also observed: MXHT, PF, RFD, and PP (all p < 0.001). Finally, statistically significant extremities x jump-type interaction effects were obtained for MXHT, PF, RFD, and PP (all p < 0.001). These gymnasts showed better performances in CJs relative to SJs, but performances were unexpectedly poorer in the DJs. Despite using rebound-type jumps in tumbling and vaulting with UE and LE, the DJs did not appear to capture the athletes` stretch-shortening cycle skill or may reflect poor stretch-shortening cycle skill.